Tanggung Jawab Terhadap Barang Bukti Yang Disita Dalam Proses Pemeriksaan Perkara Pidana - Derry Angling Kesuma (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2021)
Based on the explanation above, the material objects that have research power are goods that are the target of a crime, the proceeds of a crime, the tools used by the crime, as well as goods to aggravate or alleviate the defendant's guilt. Then it is further explained that the management of evidence is the procedure or process for receiving, securing, maintaining, releasing and destroying confiscated objects from a special room or place for storing evidence.The function of the place for storing confiscated objects is a place for objects confiscated by the State for the purposes of the judicial process. In the Rupbasan, objects must be kept for the purposes of evidence in the examination at the level of investigation, prosecution and examination in court, including items declared confiscated based on a judge's decision. The use of confiscated objects for the purposes of investigation, prosecution and examination in court, there must be a request letter from the official who is legally responsible for the confiscated objects. The release of the spoils to implement a court decision that has obtained permanent legal force, is carried out at the request of the prosecutor in writing. The destruction of the spoils is carried out by the Prosecutor, and witnessed by the Head of the Rupbasan.